Special Issue "Anticancer Drugs" - Mary J. Meegan; Niamh M. O'Boyle (MDPI AG, 2019)
The focus of this Special Issue of Pharmaceuticals is on the design, synthesis, and molecular mechanism of action of novel antitumor, drugs with a special emphasis on the relationship between the chemical structure and the biological activity of the molecules. This Special Issue also provides an understanding of the biologic and genotypic context in which targets are selected for oncology drug discovery, thus providing a rationalization for the biological activity of these drugs and guiding the design of more effective agents. In this Special Issue of Pharmaceuticals dedicated to anticancer drugs, we present a selection of preclinical research papers including both traditional chemotherapeutic agents and newer more targeted therapies and biological agents. We have included articles that report the design of small molecules with promising anticancer activity as tubulin inhibitors, vascular targeting agents, and topoisomerase targeting agents, alongside a comprehensive review of clinically successful antibody-drug conjugates used in cancer treatment.